Optical communications : - Franz, J.H. (Alpha Science International, 2000)
This book covers analysis, design, optimization and application aspects of optical communications. Emphasis is placed on optical sources, fibers, and detectors, laser phone noise and polarization functions, optical amplifiers, and more